Quadrangular Space Syndrome: a systematic review of surgical and medical therapeutic advances - Sundip Charmode; Shelja Sharma; Sudhir Kushwaha; Simmi Mehra; Shalom Philip; Ranjna Janagal; Pratik Amrutiya (AOSIS, 2023)
Background: The axillary nerve and posterior circumflex humeral artery are compressed in Quadrangular Space Syndrome (QSS), which can be treated with conservative approaches or surgical decompression in recalcitrant instances. There are no clear guidelines for determining which surgical method is optimal for treating QSS and other disorders that mirror QSS. Objective: The goal of this study is to grade and review past, current, and planned medicinal and surgical care modalities for QSS. Materials and Methods: The review protocol is registered with PROSPERO (ID: CRD42022332766). To identify recent advances in the methods/techniques of medical and surgical management of QSS, PubMed and Medline databases were searched until March 2022 for publications, including case studies, case reports, and review articles, using medical subject headings terms like quadrilateral space syndrome, surgical management, and medical management. Throughout the study, all the authors scrupulously followed a well-developed registered review process and the risk of bias in systematic reviews guidance tool. Data on proposed medical and surgical management methods/techniques were compiled, and each was analyzed based on the underlying neuro-vascular systems. Results: There were 88 items found in the first search. Following applying the inclusion and exclusion criteria, 16 papers were chosen for synthesis in the review study after a thorough assessment. Three studies (conservative and advanced) focused on medical care of QSS, while 12 articles (prior, current, and newer) focused on surgical management of QSS. Only four of the 15 studies reviewed proposed different surgical approaches/techniques for surgical decompression in QSS. Conclusions: There were two regularly used surgical procedures discovered, one anterior/delto-pectoral and the other posterior/ scapular. The anterior route is more technically straightforward and can be employed for surgical QSS decompression.